STUDY ON DYNAMIC RESPONSE OF CANTILEVER COLUMN STRUCTURE WITH LUMPED MASS ON A PONTOON DUE TO HARMONIC LOAD AS A SIMULATION APPROACH FOR FLOATING WIND TURBINE RESPONSE TO WATER WAVES - D. P. Tambunan, Olivia
In this final project, a study on the dynamic response of a cantilever column structure with a lumped mass at its top standing on an elastic foundation due to a harmonic load will be conducted using the matrix method. The concept of a structure on the ground connected by an elastic foundation and subjected to harmonic loads is a model approach that idealizes the phenomenon of floating wind turbine structures subjected to harmonic loads from ocean waves. The dynamic response of the structure is simulated using the Julia Language Programming computer program based on numerical calculations of the Finite Element Method (FEM). Subsequently, the resulting dynamic response of the structure is evaluated numerically using the Newmark Method. The response results are verified against references from certain literature for similar cases. A parametric study is then conducted on the considered case to observe the influence of specific parameters on the dynamic response of the structure. The developed computer program can simulate a representation of the dynamic response of floating wind turbine structures on a pontoon to wave loads.